The moon also sets - Ogbu, Michael Osita (Nairobi : East African Educational Publishers, 2002)
"A ... story set in Isiakpu, a typical African village, and at the University of Embakassi, a modern African university. It revolves around two Nigerian women, mother and daughter, who struggle to survive in a male chauvinist society where both tradition and modernity confront them with daunting challenges"--
Keywords: Nigerian fiction (English); Women -- Africa -- Fiction; Mothers and daughters -- Fiction